Optimizing Malaysian AEC’s organizational team rework productivity using minimal collaborative technology during industrialized project delivery - Ibrahim, Rahinah; Abdul Ghafar, Maszura (UPM Press, 2021)
CITP 2016-2020 Strategic and SDG 17 Sustainable development through global partnerships has been the driving force for architects, engineers, and contractors (AEC) professionals to opt for global industrialized project delivery in the future. The purpose of this study is to identify the baseline communication preferences that can help policy makers and building professionals to prepare themselves to export their professional services in delivering transdisciplinary global project implementation. The case study found that AEC’s professional culture, method of knowledge transfer, and educational programs could affect several dimensions of their beliefs and values in ways of delivering global transdisciplinary projects. Results include documentation of triadic and dyadic rework iterations communication culture of professionals. This study is limited to the effect of a professional’s human factor during IPD’s design development stage. The study recommends formalizing AEC professionals’ communication system through application in integrated design studio education program in preparing future Malaysian AEC transdisciplinary global practice.